Digital Entrepreneurship Training and Entrepreneurial Capability Development among Community-Based Participants - Santos, Angelo (International Review of Management and Marketing, 2026)
Technology-enabled training has become an important mechanism for expanding entrepreneurship development and business capability-building beyond formal academic settings. This study evaluated Project BIZ-SIKAP (Business Innovation and Zeal for Sustainable Income, Knowledge, and Progress) as a university-led, technology-enabled entrepreneurship training program for community-based participants. Specifically, it examined participation, perceived learning gains, and participant satisfaction across a four-session online training series covering management, production and operations, marketing, supply and demand analysis, and financial management. The study employed a descriptive-evaluative design using documentary and program-based quantitative data drawn from the approved project proposal, accomplishment and terminal reports, attendance records, training evaluation summaries, and monitoring reports. Participants included business owners, aspiring entrepreneurs, professionals, and students. The findings indicate that the program was successfully implemented, attracted sustained participation, and generated positive learning gains and high satisfaction across all training sessions. Qualitative feedback further suggests that participants valued the practical relevance of the topics, the clarity of instruction, and the usefulness of the training for business-related decision-making. At the same time, the results indicate the need to strengthen interactivity, technical delivery, learner support, and follow-up mentoring, particularly for more technical content areas such as financial management. Overall, the study shows that digitally delivered entrepreneurship training can serve as a flexible and practice-oriented approach to entrepreneurial capability development among community participants. The findings offer practical implications for universities, trainers, and entrepreneurship support institutions seeking to design scalable technology-enabled training initiatives for small-business and aspiring entrepreneur communities.